Group and Single Pedestrian Behavior in Crowd Dynamics. Issue 1 (2016) - Do, Truong; Haghani, Milad; Sarvi, Majid
An analytical study was proposed in this paper to explore various behavioral aspects of group and single pedestrians. The results were obtained from reviewing the literature and studying primary data. Data collected from field surveys, direct observations, and video recordings were analyzed to produce the following findings. For crowds with densities between 0.4 and 0.8 persons per square meter, individuals walked faster than groups, on average. There was also significant evidence to suggest that individuals were likely to have more trajectory changes than groups. As the crowd density got higher, the likelihood of pedestrians splitting from groups of two decreased. With higher crowd densities, the rate at which split members came back to the group decreased. More individual pedestrians chose spacious stairs; groups of two were more likely to go for escalators.